Effects of mold pressure on mechanical, microstructures, oxidation behavior, and thermodynamic properties of an Al-based alloy - Kaplan, M; Yakuphanoğlu, Fahrettin; Yildiz, A (Taylor & Francis Inc, 2006)
In this study, the effects of mold pressure variation on the microstructure, mechanical, oxidation behavior, and thermodynamics properties of an AlSi12CuNi alloy have been investigated by means of optical microcopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, differential thermal analysis, and thermo-gravimetric analysis techniques. It is observed that hardness and tensile strength of the alloys increase as die-casting mold pressure increases due to an improvement in the distribution pattern of secondary phases and reduction in porosity. Oxidation behavior parameters and thermodynamic parameters such as formation enthalpy, heat capacity, and entropy are determined from TGA and DTA. It is found that mold pressure also has a significant effect on the oxidation behavior and thermodynamic parameters.
Keywords: Al-Si alloys; die-casting; differential thermal analysis; formation enthalpy; heat capacity; mechanical; microstructure; mold pressure; optical microcopy; oxidation behavior; phase structure; scanning electron microscopy; thermodynamic parameter; thermo-gravimetric analysis; X-ray diffraction